Combinable products, price discrimination, and collusion - Hendrik Döpper; Alexander Rasch (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2022)
We analyze the effect of different pricing schemes on horizontally differentiated firms' ability to sustain collusion when customers have the possibility to combine (or mix) products to achieve a better match of their preferences. To this end, we compare two-part tariffs with linear prices and quantity-independent fixed fees in two different scenarios. First, we consider exogenously determined pricing schedules such as in the case of legal or third-party restrictions. We find that the additional price component of the two-part tariff makes it more difficult to sustain collusion. Additionally, the pricing schedule that is most beneficial for customers in absence of collusion harms customers most in presence of (partial) collusion. Second, we consider the scenario in which firms endogenously choose collusive tariffs. We find that firms can commit to using only the fixed price component of the two-part tariff to facilitate collusion at maximum prices. However, once we consider partial collusion, firms prefer to use both price components of the two-part tariffs. We discuss policy implications in the context of the media and entertainment industry.
Keywords: D43; L13; L41; L82; 330; Collusion; Combinable products; Media markets; Mixing; Price discrimination; Two-part tariff